Financial markets and public information - Storkenmaier, Andreas (KIT Scientific Publishing, 2021)
The last decades have seen dramatic changes in trading technology and the way that financial markets operate. As trading technology advances, news providers have kept pace and deliver news to market participants around the world within fractions of a second using electronic systems. Currently, most news is still interpreted by humans but news providers have started to offer newswire products with machine learning systems that specifically cater to algorithmic traders. In practice, newswire messagesmake up a major part of the public information set available to investors. This book studies how newswire messages impact modern electronic equity markets.